KUALITAS KE PROFESSIONAL-AN PROFESI BIDANG KOMUNIKASI (Study Deskriptif Tanggapan User Terhadap Alumni Program Studi D3 Humas Universitas Negeri Jakarta) - Wina Puspita Sari; Asep Sugiarto (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2018)
Asean Economic Community (AEC) impacts the area of employment become more competitive. Indonesia has to improve human resources through education. University has to create professional workers to compete with other ASEAN country labors. Prodi DIII Public Relations in Universitas Negeri Jakarta have graduated public relations diploma since 2007. They have worked in several communication industries as a public relations officer. We have to know how professional they are according evaluation of their managers. Indicators of professional status include 1. spesialized educational preparation to acquire unique knowledge and skill. 2. A body of theory-based knowledge, developed through research, that provides us principles of appropriate public relations practice. 3. Code of ethic and standards of performance established and enforced by a self governing association of colleagues. 4. Autonomy in practice and acceptance of personal responsibility by practitioners. 5. Recognition by the community of a unique and essential service. This research used qualitative perpective and descriptive method. Primery data are obtained by doing depth interview with key informan and informan. The results are our alumni do several pr activities in qualification of public relations competence schema from Lembaga Sertifikasi Profesi Public Relations Indonesia. They are in different level spread from junior, middle, expert or managerial according their working period. Evaluation of their managers are good. Our alumni have ability to finish their duties. They have good mental attitude. They never break the rules or cod of conduct. But they still have to practice a lot and guidance. The conclusions, the evaluation of alumni of UNJ DIII Public Relations are good. They are professional according their job descriptions but they still have to practice a lot. To increase the status, writer suggest to adjust our alumni with sertificate of competence from sertifications institutions of pr. Key Word : AEC, professional status, public relation profession